Critical Thinking Across The Curriculum : Developing critical thinking skills, literacy and philosophy in the primary classroom. - Leicester, Mal (McGraw-Hill International (UK) Ltd., 2010)
This exciting, practical book is an essential resource for developing literacy, philosophy and thinking skills in the primary classroom.